2022
DOI: 10.3390/nu14061194
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Composition of a Co-Culture of 10 Probiotic Strains (OMNi BiOTiC® AAD10) and Effects of Its Postbiotic Culture Supernatant

Abstract: Background: We aimed to gain insights in a co-culture of 10 bacteria and their postbiotic supernatant. Methods: Abundances and gene expression were monitored by shotgun analysis. The supernatant was characterized by liquid chromatography mass spectroscopy (LC-MS) and gas chromatography mass spectroscopy (GC-MS). Supernatant was harvested after 48 h (S48) and 196 h (S196). Susceptibility testing included nine bacteria and C. albicans. Bagg albino (BALBc) mice were fed with supernatant or culture medium. Fecal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…In another clinical study, this multi-strain probiotic positively influenced the gastrointestinal tract of patients with diarrhoea-predominated irritable bowel syndrome [120]. In another study, the multi-strain postbiotic supernatant of the dietary supplement OMNi-BiOTic AAD10 with similar composition exhibited positive antibacterial and antifungal effects in vitro [121].…”
Section: Discussionmentioning
confidence: 90%
“…In another clinical study, this multi-strain probiotic positively influenced the gastrointestinal tract of patients with diarrhoea-predominated irritable bowel syndrome [120]. In another study, the multi-strain postbiotic supernatant of the dietary supplement OMNi-BiOTic AAD10 with similar composition exhibited positive antibacterial and antifungal effects in vitro [121].…”
Section: Discussionmentioning
confidence: 90%
“…Promisingly, the culture supernatant of B. fragilis appears to have similar effects, suppressing high expression of IL-1β and IL-6 induced by TNF-α and increasing the anti-inflammatory factor IL-10, whereas conversely promoting and superimposing the expression of IL-8 induced by TNF-a, indicating that the mechanisms by which the anti-inflammatory effects are exerted by B. fragilis itself and the metabolites might be distinct. A recent study by Bernhard 45 investigated the composition of 10 strains of probiotic bacteria (OMNi bio®AAD10) and the effect of their supernatant after cultivation. They have shown that the supernatant of these bacteria had excellent antibacterial and antifungal effects and promoted the growth of different bacteria in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Promisingly, the culture supernatant of B. fragilis appears to have similar effects, suppressing high expression of IL-1β and IL-6 induced by TNF-α and increasing the anti-in ammatory factor IL-10, whereas conversely promoting and superimposing the expression of IL-8 induced by TNF-a, indicating that the mechanisms by which the anti-in ammatory effects are exerted by B. fragilis itself and the metabolites might be distinct. A recent study by Bernhard [55] investigated the composition of 10 strains of probiotic bacteria (OMNi bio®AAD10) and the effect of their supernatant after cultivation. They have shown that the supernatant of these bacteria had excellent antibacterial and antifungal effects and promoted the growth of different bacteria in vivo.…”
Section: Discussionmentioning
confidence: 99%